Fluid replacement: 1
Fluid ingestion remains of paramount importance for more lengthy exercise periods, especially those of greater than two hours in the heat and high humidity. In such cases, the amount of fluid lost as sweat is sufficient to make impaired performance a certainty, and dehydration and hyperthermia distinct possibilities. Finally, pre-exercise (up to two hours before) and post-exercise fluid intake also remain priorities for all exercise types and durations when optimum performance and recovery are required.